Variola minor in coalfield areas of England and Wales, 1921–34: geographical determinants of a national smallpox epidemic that spread out of effective control - Smallman-Raynor, Matthew; Rafferty, S.; Cliffe, Andrew (Elsevier, 2017)
This paper uses techniques of binary logistic regression to identify the spatial determinants of the last national epidemic of smallpox to spread in England and Wales, the variola minor epidemic of 1921–34. Adjusting for age and county-level variations in vaccination coverage in infancy, the analysis identifies a dose-response gradient with increasing odds of elevated smallpox rates in local government areas with (i) medium (odds ratio [OR] = 5.32, 95% Confidence Interval [95% CI] 1.96–14.41) and high (OR = 11.32, 95% CI 4.20–31.59) coal mining occupation rates and (ii) medium (OR = 16.74, 95% CI 2.24–125.21) and high (OR = 63.43, 95% CI 7.82–497.21) levels of residential density. The results imply that the spatial transmission of variola virus was facilitated by the close spatial packing of individuals, with a heightened transmission risk in coal mining areas of the country. A syndemic interaction between common respiratory conditions arising from exposure to coal dust and smallpox virus transmission is postulated to have contributed to the findings. We suggest that further studies of the geographical intersection of coal mining and acute infections that are transmitted via respiratory secretions are warranted.